Validation of two pressure ulcer risk assessment scales among chinese ICU patients - Liu,Ming (2013)
Context: A valid and reliable risk assessment scale is considered to be an essential tool in pressure ulcer prevention. The commonly used pressure ulcer risk scales in Intensive Care Unit (ICU) patients are the Braden Scale and the Cubbin & Jackson Scale. Aim: To compare and validate the Braden and Cubbin & Jackson pressure ulcer risk scales among Chinese ICU patients. Method: A longitudinal research design was proposed in which the Braden Scale and the Cubbin & Jackson Scale were simultaneously used to collect 139 ICU patients data. The area under the curve (AUC) of the receiver operating characteristic (ROC) method was employed to evaluate the overall validity of the scales. Results: Eleven patients (7.91%) developed pressure ulcers. Based on the cut-off point of 16 for the Braden Scale and 24 for the Cubbin & Jackson Scale, the sensitivity, specificity, positive predictive value and negative predictive value for the Braden Scale were 91.7%, 63.0%, 19.0%, 98.8%, respectively, and 33.3%, 95.3%, 40.0%, 93.8% for the Cubbin & Jackson Scale. The AUC was 0.155 for Braden scale and 0.098 for the Cubbin & Jackson Scale. Conclusion: The Braden Scale has high sensitivity and negative predictabiity, whereas the Cubbin & Jackson Scale has high specificity. The Braden Scale is better than the Cubbin & Jackson Scale in terms of overall validity.